Optical Manipulation of Lanthanide-Doped Nanoparticles: How to Overcome Their Limitations - Ortiz-Rivero, Elisa; Labrador-Páez, Lucía; Rodríguez-Sevilla, Paloma; Haro-González, Patricia (Frontiers in Chemistry, 2020)
Since Ashkin’s pioneering works, optical tweezers have become an essential tool to immobilize and manipulate micro- and nano-scale objects. The use of optical tweezers is key for a variety of applications, including single molecule spectroscopy, colloidal dynamics, tailored particle assembly, protein isolation, high-resolution surface studies, controlled investigation of biological processes, and surface enhanced spectroscopy. In recent years, optical trapping of individual sub-100 nm objects has got the attention of the scientific community. In particular, the three-dimensional manipulation of single lanthanide-doped luminescent nanoparticles is of great interest due to the sensitivity of their luminescent properties to environmental conditions. Nevertheless, it is really challenging to trap and manipulate single lanthanide-doped nanoparticles due to the weak optical forces achieved with conventional optical trapping strategies. This limitation is caused, firstly, by the diffraction limit in the focusing of the trapping light and, secondly, by the Brownian motion of the trapped object. In this work, we summarize recent experimental approaches to increase the optical forces in the manipulation of lanthanide-doped nanoparticles, focusing our attention on their surface modification and providing a critical review of the state of the art and future prospects.